Last chance for victory Robert E. Lee and the Gettysburg campaign - Bowden, Scott (Da Capo Press, 2001)
Gettysburg is the most written about battle in American military history. Generations after nearly 50,000 soldiers shed their blood there, serious and fundamental misunderstandings persist about Robert E. Lee's generalship during the campaign and battle. Most are the basis of popular myths about the epic fight.Last Chance for Victory: Robert E. Lee and the Gettysburg Campaign addresses these issues by studying Lee's choices before, during, and after the battle, the information he possessed at the time and each decision that was made, and why he acted as he did. Even options open to Lee that he did not act upon are carefully explored from the perspective of what Lee and his generals knew at the time. Some of the issues addressed include:Whether Lee's orders to Jeb Stuart were discretionary and allowed him to conduct his raid around the Federal army. The authors conclusively answer this important question with the most original and unique analysis ever applied to this controversial issue;Why Richard Ewell did not attack Cemetery Hill as ordered by General Lee, and why every historian who has written that Lee's orders to Ewell were discretionary are dead wrong;Why Little Round Top was irrelevant to the July 2 fighting, a fact Lee clearly recognized;Why Cemetery Hill was the weakest point along the entire Federal line, and how close the Southerners came to capturing it;Why Lee decided to launch en echelon attack on July 2, and why most historians have never understood what it was or how close it came to success;Last Chance for Victory will be labeled heresy by some, blasphemy by others, all because its authors dare to call into question the dogmas of Gettysburg. But they do so carefully, using facts, logic, and reason to weave one of the most compelling and riveting military history books of our age.Readers will never look at Robert E. Lee and Gettysburg the same way again.